2017
DOI: 10.1152/ajplung.00055.2017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ventilation-induced lung injury on the structure and function of lamellar bodies

Abstract: Alterations to the pulmonary surfactant system have been observed consistently in ventilation-induced lung injury (VILI) including composition changes and impairments in the surface tension reducing ability of the isolated extracellular surfactant. However, there is limited information about the effects of VILI on the intracellular form of surfactant, the lamellar body. It is hypothesized that VILI leads to alterations of lamellar body numbers and function. To test this hypothesis, rats were randomized to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
0
16
2
Order By: Relevance
“…Milos et al found quite recently that high tidal volume ventilation (VILI) lead to significant alterations of lamellar body (LB) numbers and function . An impaired ability of reducing surface tension for the LB isolated from the VILI group was observed, the LB number and LB area was also significantly decreased, suggesting that LB changes after VILI contribute to impairments in surface tension reduction within the alveolar hypophase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milos et al found quite recently that high tidal volume ventilation (VILI) lead to significant alterations of lamellar body (LB) numbers and function . An impaired ability of reducing surface tension for the LB isolated from the VILI group was observed, the LB number and LB area was also significantly decreased, suggesting that LB changes after VILI contribute to impairments in surface tension reduction within the alveolar hypophase.…”
Section: Discussionmentioning
confidence: 99%
“…(VILI) lead to significant alterations of lamellar body (LB) numbers and function. 19 An impaired ability of reducing surface tension for the LB isolated from the VILI group was observed, the LB number and LB area was also significantly decreased, suggesting that LB changes after VILI contribute to impairments in surface tension reduction within the mice. 25 Another study showed that inhalation of BUD could significantly increase the SP-B precursors in the bronchoalveolar lavage fluids of patients with chronic lung diseases.…”
Section: Milos Et Al Found Quite Recently That High Tidal Volume Ventmentioning
confidence: 91%
“…Conversely, surfactant dysfunction may also be a direct consequence of abnormal alveolar micromechanics. Mechanical but also spontaneous ventilation can be associated with undue alveolar strain and large changes of the alveolar surface area which has been shown to be responsible for alterations of the intracellular and intra-alveolar surfactant system and finally acute lung injury (Milos et al 2017 ; Veldhuizen et al 2002 ; Mascheroni et al 1988 ). Mechanical ventilation with high tidal volumes to induce abnormally high strain of the lung results in a conversion of biophysically active large aggregates of surfactant to inactive small aggregates of surfactant within the airspaces (Veldhuizen et al 2002 ).…”
Section: Dysfunction: Lung Injury and Fibrosismentioning
confidence: 99%
“…In experimental animal models, the choice of intravenous fluid maintenance varies widely [9, 1921]. For example, in rat models rates starting at 1 ml/kg/hour [9] up to 10 ml/kg/hour [11, 21] have been used, and sometimes even with volumes varying between animals within a study [11]. It is an interesting realization, that while evidence of the adverse effects of fluid overload in ARDS patients is accumulating [1, 4], fluid strategies in animal models are not already under a stricter, well-formed policy.…”
Section: Discussionmentioning
confidence: 99%
“…Given the above mentioned important influences of fluid treatment for the course of ARDS in humans it is remarkable that so far the potential effects of intravenous fluid maintenance strategies on markers of acute lung injury in animals have not been addressed. There is currently no protocol or consensus regarding a standard fluid strategy, resulting in the use of a wide range of fluid rates within models using the same animal species [9, 11]. Likewise, the potential effect of age-related differences in the response to fluids during acute lung injury remains unknown.…”
Section: Introductionmentioning
confidence: 99%